A tunable volatile organic compound sensor by using PtOx/GQDs/TiO2 nanocomposite thin films at room temperature under visible-light activation. Issue 63 (16th August 2017) - Shao, Shaofeng; Chen, Yunyun; Huang, Shenbei; Jiang, Fan; Wang, Yunfei; Koehn, Ralf
Abstract : Pt/GQDs/TiO2 nanocomposite thin film-based gas sensors show tunable VOC sensing behaviour at room temperature under visible-light activation. Abstract : In this work, a PtO x /GQDs/TiO2 nanoporous thin film with high sensitivity and excellent selectivity at room temperature is fabricated in situ on a sensor device by using an oxygen-plasma treatment. PtO x /GQDs/TiO2 nanocomposite thin films exhibit distinctly different sensor responses toward oxygen-functionalized VOCs under visible-light activation. In particular, the PtO x /GQDs/TiO2 nanocomposite thin films depict a reversible change in their sensing behaviour from p-type to n-type for oxygen-functionalized VOCs as a function of the oxygen-plasma treatment, while these gas sensors present p-type sensing performance for aromatic VOCs throughout. Furthermore, the gas sensors in this work exhibit high sensitivity to isopropanol gas with a response value of up to 4.4 to 1 ppm and a short response time of 9 seconds at room temperature. The reported synthesis procedure to fabricate a tunable and sensitive VOC sensor may be extended to a potential real-world application in breath diagnosis.